FUNCTIONS OF ENGLISH TABOO WORDS USED IN READY OR NOT MOVIE - Ni Made, Hyunika Santi (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
One of human communication tools is language. Language can be divided into two types, formal and informal language. Taboo words are included in informal language, since taboo words cannot be spoken in all situations or places. Taboo words have their own functions when spoken and used by several people. The aim of this study is to find out the functions of taboo words that are used in “Ready or Not” movie. This study used theory from Wardhaugh (2006: 239) to find out the functions of taboo words. The method being used in this study is a descriptive qualitative method and observation technique to collect the data. In general, it is found three out of four functions of taboo words, those are to show contempt, to draw attention to oneself, and to be provocative.